High-Yield Electrosynthesis of Hydrogen Peroxide from Oxygen Reduction by Hierarchically Porous Carbon - Liu, Yanming; Quan, Xie; Fan, Xinfei; Wang, Hua; Chen, Shuo (Angewandte Chemie International Edition, 2015)
H2O2 production by electroreduction of O2 is an attractive alternative to the current anthraquinone process, which is highly desirable for chemical industries and environmental remediation. However, it remains a great challenge to develop cost‐effective electrocatalysts for H2O2 synthesis. Here, hierarchically porous carbon (HPC) was proposed for the electrosynthesis of H2O2 from O2 reduction. It exhibited high activity for O2 reduction and good H2O2 selectivity (95.0–70.2 %, most of them >90.0 % at pH 1–4 and >80.0 % at pH 7). High‐yield H2O2 generation has been achieved on HPC with H2O2 concentrations of 222.6–62.0 mmol L−1 (2.5 h) and corresponding H2O2 production rates of 395.7–110.2 mmol h−1 g−1 at pH 1–7 and −0.5 V. Moreover, HPC was energy‐efficient for H2O2 production with current efficiency of 81.8–70.8 %. The exceptional performance of HPC for electrosynthesis of H2O2 could be attributed to its high content of sp3‐C and defects, large surface area and fast mass transfer. The electroreduction of O2 is achieved with hierarchically porous carbon (HPC) to give H2O2. It exhibits good selectivity, a high production rate, and current efficiency for the electrosynthesis of H2O2 at a wide range of pH values. The correlation between H2O2 production rate and sp3‐C atoms and defects was explored. This provides an effective method for tuning the activity of carbon materials for the selective electrosynthesis of H2O2. RE=reference electrode.